The Effect of Innovative Leadership and Creative Leadership to Organizational Learning, Organizational Adaptation and Adaptive Performance - Riza, M Faisal; Nimran, Umar; Musadieq, M. Al; Utami, Hamidah Nayati (JPAS (Journal of Public Administration Studies), 2020)
An integrative model of the influence of innovative leadership and creative leadership on adaptive performance was developed and tested. Organizational learning, and organizational adaptation were treated as intermediary variables. To achieve the purpose of the research, the model was developed as indicated and analyzed using SEM with Smart-PLS. The results, suggest that the effect of innovative leadership on adaptive performance is positive and insignificant, this means that the better innovation leadership will tend to increase adaptive performance, even though the increase is not significant. But rest variables have direct effect positive and significant, as well as indirectly effect. Specifically, innovative leadership and creative leadership affect adaptive performance indirect through their effects on organizational learning, and organizational adaptation are positive and significant. In general, findings of the study support major findings of previous studies, extend and integrate previous models, in which they are discussed.